2020
DOI: 10.1021/acs.energyfuels.0c01608
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Fabrication of Fluorine-Doped Graphite Derived from a Low-Grade Microcrystalline Graphite Ore for Potassium-Ion Batteries

Abstract: Graphite has been considered as a promising anode material of potassium-ion batteries (KIBs), the practical applications of which are impeded because of the unsatisfactory cycling stability and poor rate capability. In this study, the favorable effect of fluorine-doping on the K-storage performance of graphite is demonstrated. For a more practical application, a low-grade microcrystalline graphite (MG) ore is chosen as the raw material and is purified through a facile hydrofluoric acid solution immersion metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…By comparing the profile characteristics of the three electrodes [Figures a,b and S10a (SI)], one can find that the CV curve of the FC@NMG-3 electrode exhibits a mixed characteristic, which combines the features of h-NMG electrode and FC electrode. In the first cathode scan, a broad peak in the range from 0.2 to 1.1 V is attributed to the irreversible reactions caused by the decomposition of electrolyte and the formation of a SEI layer . It is noted that the integral area of the above cathode peak is larger than that of h-NMG, which implies that more irreversible reactions occur for the SEI film formation during the first cycle.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…By comparing the profile characteristics of the three electrodes [Figures a,b and S10a (SI)], one can find that the CV curve of the FC@NMG-3 electrode exhibits a mixed characteristic, which combines the features of h-NMG electrode and FC electrode. In the first cathode scan, a broad peak in the range from 0.2 to 1.1 V is attributed to the irreversible reactions caused by the decomposition of electrolyte and the formation of a SEI layer . It is noted that the integral area of the above cathode peak is larger than that of h-NMG, which implies that more irreversible reactions occur for the SEI film formation during the first cycle.…”
Section: Resultsmentioning
confidence: 96%
“…The heteroatom doping can increase the structural disorder of the graphite surface and provide additional active sites for potassium storage. Moreover, the introduction of heteroatoms further increases the graphite interlayer space, which is more conducive to alleviate the volume expansion caused by the intercalation of large-radius K ions into the graphite layers. Recently, a fluorine-doped graphite was obtained directly from a natural graphite mine through a simple immersion treatment with HF acid . The F-doping creates a very positive effect of the interlayer distance enlargement of the (002) plane (from 3.356 to 3.461 Å), an improved electrode surface condition, and an accelerated charge transfer/K ion diffusion kinetics, thus enhancing the reversible capacity, cyclic stability, and rate performance of the graphite electrode.…”
Section: Introductionmentioning
confidence: 99%
“…Our society has been drastically changed by lithium-ion batteries (LIBs) since their first commercialization in the early 1990s. However, due to the environmental and ethical issues of raw materials (i.e., lithium, and cobalt) , and increasing demands for lower cost and high safety, emerging battery technologies such as sodium-ion batteries (NIBs) and potassium-ion batteries (KIBs) , have become more attractive. Among them, sodium-ion batteries (NIBs) are regarded as efficient alternatives to LIBs as they share the same working chemistry and accept a walk-in technology that can benefit from the already existing LIB manufacturing facilities .…”
mentioning
confidence: 99%
“…The authors reveal that the excellent rate capability and cycling stability are attributed to the synergistic effects of F in graphene, including the high specific surface area, fast ions and electrons transportation, and abundant active sites for K ions storage. Zhao et al 155 reported a facile hydrofluoric acid solution immersion method to purify the low-grade microcrystalline graphite ore. The purity of modified graphite could be as high as 98.59 wt% with the effective F-corporation of the content about 1.02%, which could enlarge the interlayer distance and further lead to a fast K-ion diffusion and weak volume change.…”
Section: Graphite Carbon Materialsmentioning
confidence: 99%